2013
DOI: 10.1017/s0033291713001657
|View full text |Cite
|
Sign up to set email alerts
|

Does neuroticism make you old? Prospective associations between neuroticism and leukocyte telomere length

Abstract: High neuroticism is significantly and prospectively associated with telomere attrition independent of lifestyle and other risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…This view is supported by mounting evidence from epidemiological studies showing that people that have had various types of negative experiences have shorter telomeres than age-matched controls, and that the effects might be dose dependent [38,39]. For example, anxiety [40], depression [41], neuroticism [42], pessimism [43], childhood exposure to violence [44], family disruption [25], chronic pain [45,46] are all associated with shorter telomeres. In the first study of this type, Epel and coworkers [47] showed that TL in female caregivers was negatively correlated both with the number of years spent as a caregiver and the subjective perceived level of stress.…”
Section: Measurement Of Telomeresmentioning
confidence: 97%
“…This view is supported by mounting evidence from epidemiological studies showing that people that have had various types of negative experiences have shorter telomeres than age-matched controls, and that the effects might be dose dependent [38,39]. For example, anxiety [40], depression [41], neuroticism [42], pessimism [43], childhood exposure to violence [44], family disruption [25], chronic pain [45,46] are all associated with shorter telomeres. In the first study of this type, Epel and coworkers [47] showed that TL in female caregivers was negatively correlated both with the number of years spent as a caregiver and the subjective perceived level of stress.…”
Section: Measurement Of Telomeresmentioning
confidence: 97%
“…It is well known that physical activity is associated with healthy aging and reduced risk for a number of chronic conditions [ 32 ], though the relationship between physical activity and telomere length remains unclear. Evidence supports an inverse relationship between telomere length and chronic pain [ 33 , 34 ] and various psychological stresses [ 35 39 ]. Interestingly, in a study that measured stress levels in both sedentary and physically active individuals, perceived stress among sedentary individuals was negatively associated with telomere length, whereas among physically active individuals, perceived stress was not related to telomere length [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Telomere length is negatively correlated with age (Müezzinler et al, 2013) and positively correlated with educational attainment (Steptoe et al, 2011) and, on average, longer telomeres are found in females relative to males (Gardner et al, 2014), and in African Americans relative to Whites (Hunt et al, 2008; Needham et al, 2013). Furthermore, telomere length is associated with personality factors such as neuroticism (van Ockenburg et al, 2014), and health behaviors and lifestyle factors such as cigarette smoking (Valdes et al, 2005) and body mass index (BMI) (Müezzinler et al, 2014). Because many of the variables that covary with telomere length are also associated with the probability of marital disruption (Kendler et al, 2002; Kurdek, 1993; Roberts et al, 2007; Tucker et al, 1998), we were interested in evaluating the incremental association between marital disruption and salivary telomere length, holding constant demographic and socioeconomic variables, neuroticism, cigarette smoking, BMI, and stressors that were unlikely to result from marital disruption but that could potentially contribute to the increased probability of both marital disruption and telomere shortening (i.e., childhood traumatic life events, traumatic life events, other stressful life events).…”
mentioning
confidence: 99%